High sensitivity coulomb force type aluminum oxide electrostatic chuck and method of manufacturing the same

CN123003269APending Publication Date: 2026-10-30无锡卓瓷科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611482282.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]为解决上述背景技术中提到的不足,本发明的目的在于提供高灵敏库仑力型氧化铝静电吸盘及其制造方法,以高纯氧化铝掺杂1.3~1.8wt.%改性纳米二氧化钛混合粉末为原料,通过大气等离子喷涂工艺在静电吸盘表面得到陶瓷涂层,然后通过水热反应在陶瓷涂层的孔隙和微裂纹等缺陷处原位合成二硫化钼,随后将1~1.5wt.%聚乙烯醇改性铝溶胶渗入涂层未被填充的孔隙和裂纹中,经分级干燥处理和真空烧结处理,制备得到的样品硬度高,具备良好的耐磨性能和耐腐蚀性能

Benefits of technology

本发明采用硝酸氧化来进行碳纳米管的纯化处理,然后利用钛酸四丁酯和纯化碳纳米管为原料,通过醇盐水解方法在纯化碳纳米管表面包覆一层纳米二氧化钛颗粒,由于钛酸四丁酯遇水会发生剧烈的水解,因此选择乙醇作为反应介质,加热时烧杯中的去离子水蒸发形成水蒸气慢慢地融入到含有钛酸四丁酯和纯化碳纳米管的溶液中,使钛酸四丁酯发生缓慢的水解形成纳米二氧化钛,纳米二氧化钛不断地吸附在纯化碳纳米管表面形核结晶长大,最后形成纳米二氧化钛均匀致密包裹纯化碳纳米管的结构,制备得到改性纳米二氧化钛,其中碳纳米管作为纳米增强相具有高拉伸强度,同时纳米二氧化钛包覆层改善了碳纳米管与氧化铝基体之间的界面润湿性,避免了因直接添加碳纳米管导致的团聚和界面缺陷问题,将改性改性纳米二氧化钛填充氧化铝晶界,有利于提升陶瓷涂层显微硬度和耐磨耐蚀性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003269A_ABST
    Figure CN123003269A_ABST
Patent Text Reader

Abstract

The application relates to the field of electrostatic chuck, and discloses a high-sensitivity coulomb force type alumina electrostatic chuck and a manufacturing method thereof. The manufacturing method comprises the following steps: taking high-purity alumina doped with 1.3-1.8 wt.% modified nano-titanium dioxide mixed powder as raw material, obtaining a ceramic coating on the surface of the electrostatic chuck through an atmospheric plasma spraying process, then in-situ synthesizing molybdenum disulfide with lubricating properties at the defects such as pores and micro-cracks of the ceramic coating through a hydrothermal reaction, then infiltrating 1-1.5 wt.% polyvinyl alcohol modified aluminum sol into the pores and cracks of the coating which are not filled, and finally performing grading drying treatment and vacuum sintering treatment to obtain the high-sensitivity coulomb force type alumina electrostatic chuck. The modified nano-titanium dioxide is purified by nitric acid oxidation, then a layer of nano-titanium dioxide particles is coated on the surface of the purified carbon nanotube by using tetrabutyl titanate and the purified carbon nanotube as raw material through an alkoxide hydrolysis method, and finally the prepared sample has high hardness and good wear resistance and corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrostatic chuck technology, specifically relating to a highly sensitive coulomb force type alumina electrostatic chuck and its manufacturing method. Background Technology

[0002] In semiconductor manufacturing, the processing of silicon wafers involves multiple steps, such as plasma immersion, ion doping, ion implantation, physical vapor deposition, and chemical vapor deposition. All of these require ensuring the stable fixation of the silicon wafer. Electrostatic chucks are typically used to fix the wafers. Electrostatic chucks secure the wafers through electrostatic adsorption, preventing warping and deformation, and maintaining a consistently stable adsorption force. Coulomb-type electrostatic chucks mainly consist of a conductive substrate (such as aluminum), a covering dielectric layer (usually aluminum oxide), and an electrode layer. The quality and uniformity of the dielectric layer play a crucial role in the overall performance of the chuck and the precision of wafer processing.

[0003] In existing technologies, high-purity alumina coatings, due to their high insulation properties, face problems such as delayed static dissipation, insufficient adhesion strength, and poor corrosion and wear resistance in vacuum electrostatic chuck applications. In addition to excellent corrosion and wear resistance, mechanical properties are also crucial for improving the load-bearing capacity and reliability of electrostatic chucks. Furthermore, the mismatch in the coefficients of thermal expansion between high-purity alumina material and the metal substrate makes the coating prone to peeling off due to insufficient adhesion during thermal cycling. Although it has high hardness, it is also significantly brittle, and its wear resistance degrades rapidly under frequent wafer handling and plasma erosion, further increasing the frequency of equipment maintenance. Summary of the Invention

[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide a highly sensitive Coulomb force-type alumina electrostatic chuck and its manufacturing method. Using high-purity alumina doped with 1.3~1.8 wt.% modified nano-titanium dioxide mixed powder as raw material, a ceramic coating is obtained on the surface of the electrostatic chuck through atmospheric plasma spraying. Then, molybdenum disulfide is synthesized in situ at defects such as pores and microcracks in the ceramic coating via hydrothermal reaction. Subsequently, 1~1.5 wt.% polyvinyl alcohol modified aluminum sol is infiltrated into the unfilled pores and cracks in the coating. After graded drying and vacuum sintering, the resulting sample exhibits high hardness and good wear resistance and corrosion resistance.

[0005] The objective of this invention can be achieved through the following technical solutions: A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck includes the following steps: S1. The surface of the electrostatic chuck is preheated to 100~200℃ using a high-temperature flame stream. Then, high-purity alumina doped with 1.3~1.8wt.% modified nano-titanium dioxide mixed powder is used as raw material to perform atmospheric plasma spraying on the preheated electrostatic chuck surface to obtain a ceramic coating. S2. The ceramic coating is mechanically polished with sandpaper, and then impurities in the polishing process are washed away with anhydrous ethanol. Thiourea and sodium molybdate are dissolved in deionized water and magnetically stirred for 30 minutes to obtain a mixed solution. The polished ceramic coating is immersed in the mixed solution and sonicated for 10 minutes. Then it is transferred to a vacuum drying oven and allowed to stand for 10 minutes under a pressure of -0.095 MPa. The immersion-pressure-standing step is repeated 3 times. Then it is transferred to a reaction vessel with a polytetrafluoroethylene liner and reacted at 230℃ for 48 hours to obtain a composite ceramic coating. S3. Add 1~1.5wt.% polyvinyl alcohol to the aluminum sol, stir at 85℃ until completely dissolved, and evenly coat it on the surface of the composite ceramic coating. Then, perform graded drying treatment, followed by vacuum sintering treatment to obtain a modified composite ceramic coating. Subsequently, grind and polish the obtained modified composite ceramic coating onto the surface of the original ceramic coating to prepare a highly sensitive coulomb force type alumina electrostatic chuck. The modified nano-titanium dioxide is prepared by purifying carbon nanotubes using nitric acid oxidation, and then coating the surface of the purified carbon nanotubes with a layer of nano-titanium dioxide particles using tetrabutyl titanate and purified carbon nanotubes as raw materials through an alkoxide hydrolysis method.

[0006] Preferably, the purity of the high-purity alumina is 99.999%.

[0007] Preferably, the particle size of the high-purity alumina is 25~50μm.

[0008] Preferably, the parameters of the atmospheric plasma spraying process are set as follows: voltage 60~70V, current 550~600A, argon flow rate 40~50NLPM, hydrogen flow rate 10NLPM, spraying distance 100~120mm, and powder feeding rate 25~30g / min.

[0009] Preferably, the thickness of the ceramic coating is 175~185μm.

[0010] Preferably, the preparation method of the modified nano-titanium dioxide includes the following steps: (1) Take carbon nanotubes and add them into a 68% concentrated nitric acid solution. Heat to 110°C and reflux for 12 hours. Then filter and wash with deionized water until neutral. Dry at 80°C to constant weight to obtain purified carbon nanotubes. (2) The purified carbon nanotubes were ultrasonically dispersed in a 1% sodium dodecyl sulfate aqueous solution, the water was removed by rotary evaporation and dried at 80°C. Tetrabutyl titanate was dissolved in a reactor containing an ethanol solution, and then the dried purified carbon nanotubes were added and ultrasonically vibrated for 5 min. The ultrasonically vibrated reactor was placed in a beaker containing deionized water, the mouth of the beaker was sealed with a plastic film, and the sealed beaker was placed in a water bath at 80°C for 10 h. The reaction product was washed with deionized water, filtered and dried at 100°C for 6 h, and finally calcined at 350°C for 2 h to prepare modified nano titanium dioxide.

[0011] Preferably, the length of the carbon nanotubes is 8~14μm.

[0012] Preferably, the ratio of the purified carbon nanotubes, tetrabutyl titanate, and ethanol solution is 1g:3.3g:40mL.

[0013] Preferably, the mass ratio of thiourea to sodium molybdate is 1.48:1.

[0014] Preferably, the method for preparing the aluminum sol includes the following steps: Aluminum nitrate solution was heated to 85°C in a constant temperature water bath. Ammonia solution was then added dropwise while stirring continuously until the pH value stabilized at 9.1. The solution was then removed and cooled. After the temperature dropped to room temperature, the solution was centrifuged. The lower precipitate was collected, dissolved in deionized water, and nitric acid solution was added dropwise to adjust the pH value to 3. The solution was then heated to 85°C in a water bath and stirred for 1 hour. Finally, the solution was aged for 24 hours to prepare aluminum sol.

[0015] Preferably, the concentration of the aluminum nitrate solution is 0.2 mol / L; the concentration of the ammonia solution is 2 mol / L; and the concentration of the nitric acid solution is 1 mol / L.

[0016] Preferably, the centrifugation operation is performed at a speed of 5000 r / min for 5 min, and the centrifugation is repeated 3 times.

[0017] Preferably, the parameters for the graded drying process are set as follows: first, dry at 60°C for 20 min, then dry at 80°C for 15 min, and then dry at 120°C for 15 min, and repeat 3 times.

[0018] Preferably, the parameters for the vacuum sintering treatment are set as follows: first, heat treatment at 120°C for 20 minutes, then heat treatment at 240°C for 20 minutes, and then heat treatment at 400°C for 30 minutes.

[0019] A highly sensitive coulomb force type alumina electrostatic chuck is prepared by the method described above.

[0020] The beneficial effects of this invention are: This invention employs nitric acid oxidation to purify carbon nanotubes. Then, using tetrabutyl titanate and purified carbon nanotubes as raw materials, a layer of nano-titanium dioxide particles is coated onto the surface of the purified carbon nanotubes via ethanol hydrolysis. Since tetrabutyl titanate undergoes vigorous hydrolysis upon contact with water, ethanol is chosen as the reaction medium. During heating, deionized water in the beaker evaporates, forming water vapor that slowly dissolves into the solution containing tetrabutyl titanate and purified carbon nanotubes, causing the tetrabutyl titanate to slowly hydrolyze and form nano-titanium dioxide. The nano-titanium dioxide continuously adsorbs onto the surface of the purified carbon nanotubes, nucleating and crystallizing, eventually forming a structure where nano-titanium dioxide uniformly and densely encapsulates the purified carbon nanotubes, thus preparing modified nano-titanium dioxide. The carbon nanotubes, acting as a nano-reinforcing phase, possess high tensile strength. Simultaneously, the nano-titanium dioxide coating improves the interfacial wettability between the carbon nanotubes and the alumina matrix, avoiding agglomeration and interfacial defects caused by directly adding carbon nanotubes. Filling the alumina grain boundaries with modified nano-titanium dioxide is beneficial for improving the microhardness, wear resistance, and corrosion resistance of the ceramic coating.

[0021] This invention utilizes the sol-gel method to prepare aluminum sol, and modifies the aluminum sol with 1~1.5 wt.% polyvinyl alcohol. Polyvinyl alcohol, with its special molecular structure, possesses unique interfacial compatibility in chemical conversion films, anti-corrosion coatings, and nanofillers. At the same time, it is added to the aluminum sol as a dispersant and film-forming aid by utilizing its steric hindrance and electrostatic stabilization properties to inhibit particle growth, thereby improving the film-forming performance of the aluminum sol. Furthermore, the addition of polyvinyl alcohol fills the micropores and defects in the aluminum sol coating, improving the coating density and the continuity of the microstructure. This invention employs atmospheric plasma spraying to prepare a ceramic coating on the surface of a preheated electrostatic chuck. Then, through hydrothermal reaction, molybdenum disulfide with lubricating properties is synthesized in situ at defects such as pores and microcracks in the ceramic coating, imparting excellent self-lubricating properties to the composite ceramic coating and reducing frictional wear during wafer adsorption and release. Subsequently, 1-1.5 wt.% polyvinyl alcohol-modified aluminum sol is infiltrated into the unfilled pores and cracks of the coating. After graded drying and vacuum sintering, a highly sensitive Coulomb force-type alumina electrostatic chuck is prepared, hindering the diffusion of corrosive media and ion transport, reducing the mass transfer involved in the corrosion reaction, and significantly improving the corrosion resistance life of the electrostatic chuck under harsh process environments. Furthermore, through the three-level composite structure of this invention, especially the gradient matching between the semiconductor properties of molybdenum disulfide and the dielectric properties of the alumina matrix, the interfacial polarization loss within the coating is effectively reduced. This allows the electrostatic chuck to establish a Coulomb force adsorption electric field more quickly and uniformly under operating voltage, thereby achieving highly sensitive and low-hysteresis adsorption control of the wafer. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 These are SEM images (a) of purified carbon nanotubes, SEM images (b) of modified nano-titanium dioxide, and TEM images (c) of modified nano-titanium dioxide prepared in Example 1 of this invention. Figure 2 This is the cross-sectional morphology of the sample prepared in Example 4 of the present invention. Detailed Implementation

[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0025] Example 1: A method for preparing modified nano-titanium dioxide includes the following steps: (1) Take carbon nanotubes and add them into a 68% concentrated nitric acid solution. Heat to 110°C and reflux for 12 hours. Then filter and wash with deionized water until neutral. Dry at 80°C to constant weight to obtain purified carbon nanotubes. (2) Take 1g of purified carbon nanotubes and ultrasonically disperse them in a 1% sodium dodecyl sulfate aqueous solution. Remove the water by rotary evaporation and dry them at 80℃. Take 3.3g of tetrabutyl titanate and dissolve it in a reactor containing 40mL of ethanol solution. Then add the dried purified carbon nanotubes and ultrasonically vibrate for 5min. Place the ultrasonically vibrated reactor into a beaker containing deionized water. Seal the mouth of the beaker with plastic film. Place the sealed beaker in a water bath at 80℃ for 10h. Wash the reaction product with deionized water, filter it and dry it at 100℃ for 6h. Finally, calcine it at 350℃ for 2h to prepare modified nano titanium dioxide.

[0026] Please see Figure 1 Compared with purified carbon nanotubes, it can be seen that in modified nano-titanium dioxide, nano-titanium dioxide is uniformly and densely coated on the surface of purified carbon nanotubes. There are no obvious grain boundaries between nano-titanium dioxide particles, and no agglomerated or free nano-titanium dioxide exists, indicating good coating.

[0027] Example 2: A method for preparing aluminum sol includes the following steps: 100 mL of 0.2 mol / L aluminum nitrate solution was heated to 85 °C in a constant temperature water bath. Then, 2 mol / L ammonia solution was added dropwise while stirring continuously until the pH value stabilized at 9.1. The solution was then removed and cooled. After the temperature dropped to room temperature, centrifugation was performed at a speed of 5000 r / min for 5 min, and the mixture was centrifuged 3 times. After centrifugation, the lower precipitate was taken, dissolved in deionized water, and 1 mol / L nitric acid solution was added dropwise to adjust the pH value to 3. The mixture was then heated to 85 °C in a water bath and stirred for 1 h. Finally, the mixture was aged for 24 h to prepare aluminum sol.

[0028] Example 3 A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck, comprising the following steps: S1. The surface of the electrostatic chuck is preheated to 120°C using a high-temperature flame stream. Then, using the modified nano-titanium dioxide mixed powder prepared in Example 1 with 1.3 wt.% high-purity alumina doped with it as raw material, an atmospheric plasma spraying process is performed on the preheated electrostatic chuck surface. The voltage is 60V, the current is 550A, the argon flow rate is 40NLPM, the hydrogen flow rate is 10NLPM, the spraying distance is 120mm, and the powder feeding rate is 25g / min to obtain a ceramic coating. S2. The ceramic coating was mechanically polished with SiC sandpaper, and then impurities were washed away with anhydrous ethanol. 2.77g of thiourea and 1.87g of sodium molybdate were dissolved in 80mL of deionized water and magnetically stirred for 30min to obtain a mixed solution. The polished ceramic coating was immersed in the mixed solution and sonicated for 10min. Then it was transferred to a vacuum drying oven and allowed to stand for 10min under a pressure of -0.095MPa. The immersion-pressure-standing step was repeated 3 times. Then it was transferred to a reaction vessel lined with polytetrafluoroethylene and reacted at 230℃ for 48h to obtain a composite ceramic coating. S3. Add 1 wt.% polyvinyl alcohol to the aluminum sol prepared in Example 2, stir at 85°C until completely dissolved, and uniformly coat the composite ceramic coating surface. Then, perform a graded drying treatment: first dry at 60°C for 20 min, then dry at 80°C for 15 min, and then dry at 120°C for 15 min, repeating this process 3 times. After drying, perform vacuum sintering treatment: first heat treat at 120°C for 20 min, then heat treat at 240°C for 20 min, and then heat treat at 400°C for 30 min to obtain a modified composite ceramic coating. Then, grind and polish the obtained modified composite ceramic coating onto the original ceramic coating surface to prepare a highly sensitive coulomb force type alumina electrostatic chuck.

[0029] Example 4: A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck, comprising the following steps: S1. The surface of the electrostatic chuck is preheated to 150°C using a high-temperature flame stream. Then, using the modified nano-titanium dioxide mixed powder prepared in Example 1 with 1.5 wt.% high-purity alumina doped with it as raw material, an atmospheric plasma spraying process is performed on the preheated electrostatic chuck surface. The voltage is 60V, the current is 600A, the argon flow rate is 40NLPM, the hydrogen flow rate is 10NLPM, the spraying distance is 120mm, and the powder feeding rate is 30g / min to obtain a ceramic coating. S2. The ceramic coating was mechanically polished with SiC sandpaper, and then impurities were washed away with anhydrous ethanol. 2.77g of thiourea and 1.87g of sodium molybdate were dissolved in 80mL of deionized water and magnetically stirred for 30min to obtain a mixed solution. The polished ceramic coating was immersed in the mixed solution and sonicated for 10min. Then it was transferred to a vacuum drying oven and allowed to stand for 10min under a pressure of -0.095MPa. The immersion-pressure-standing step was repeated 3 times. Then it was transferred to a reaction vessel lined with polytetrafluoroethylene and reacted at 230℃ for 48h to obtain a composite ceramic coating. S3. Add 1.2 wt.% polyvinyl alcohol to the aluminum sol prepared in Example 2, stir at 85°C until completely dissolved, and uniformly coat the composite ceramic coating surface. Then, perform a graded drying treatment: first dry at 60°C for 20 min, then dry at 80°C for 15 min, and then dry at 120°C for 15 min, repeating this process 3 times. After drying, perform vacuum sintering treatment: first heat treat at 120°C for 20 min, then heat treat at 240°C for 20 min, and then heat treat at 400°C for 30 min to obtain a modified composite ceramic coating. Then, grind and polish the obtained modified composite ceramic coating onto the original ceramic coating surface to prepare a highly sensitive coulomb force type alumina electrostatic chuck.

[0030] Example 5: A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck, comprising the following steps: S1. The surface of the electrostatic chuck is preheated to 150°C using a high-temperature flame stream. Then, using the modified nano-titanium dioxide mixed powder prepared in Example 1 with 1.8 wt.% high-purity alumina doped with it as raw material, an atmospheric plasma spraying process is performed on the preheated electrostatic chuck surface. The voltage is 60V, the current is 550A, the argon flow rate is 40NLPM, the hydrogen flow rate is 10NLPM, the spraying distance is 120mm, and the powder feeding rate is 25g / min to obtain a ceramic coating. S2. The ceramic coating was mechanically polished with SiC sandpaper, and then impurities were washed away with anhydrous ethanol. 2.77g of thiourea and 1.87g of sodium molybdate were dissolved in 80mL of deionized water and magnetically stirred for 30min to obtain a mixed solution. The polished ceramic coating was immersed in the mixed solution and sonicated for 10min. Then it was transferred to a vacuum drying oven and allowed to stand for 10min under a pressure of -0.095MPa. The immersion-pressure-standing step was repeated 3 times. Then it was transferred to a reaction vessel lined with polytetrafluoroethylene and reacted at 230℃ for 48h to obtain a composite ceramic coating. S3. Add 1.5 wt.% polyvinyl alcohol to the aluminum sol prepared in Example 2, stir at 85°C until completely dissolved, and uniformly coat the composite ceramic coating surface. Then, perform a graded drying treatment: first dry at 60°C for 20 min, then dry at 80°C for 15 min, and then dry at 120°C for 15 min, repeating this process 3 times. After drying, perform vacuum sintering treatment: first heat treat at 120°C for 20 min, then heat treat at 240°C for 20 min, and then heat treat at 400°C for 30 min to obtain a modified composite ceramic coating. Then, grind and polish the obtained modified composite ceramic coating onto the original ceramic coating surface to prepare a highly sensitive coulomb force type alumina electrostatic chuck.

[0031] Comparative Example 1: A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck, comprising the following steps: S1. The surface of the electrostatic chuck is preheated to 150°C using a high-temperature flame stream. Then, high-purity alumina doped with 1.5wt.% nano-titanium dioxide mixed powder is used as raw material to perform atmospheric plasma spraying on the preheated electrostatic chuck surface. The voltage is 60V, the current is 600A, the argon flow rate is 40NLPM, the hydrogen flow rate is 10NLPM, the spraying distance is 120mm, and the powder feeding rate is 30g / min to obtain a ceramic coating. S2. The ceramic coating was mechanically polished with SiC sandpaper, and then impurities were washed away with anhydrous ethanol. 2.77g of thiourea and 1.87g of sodium molybdate were dissolved in 80mL of deionized water and magnetically stirred for 30min to obtain a mixed solution. The polished ceramic coating was immersed in the mixed solution and sonicated for 10min. Then it was transferred to a vacuum drying oven and allowed to stand for 10min under a pressure of -0.095MPa. The immersion-pressure-standing step was repeated 3 times. Then it was transferred to a reaction vessel lined with polytetrafluoroethylene and reacted at 230℃ for 48h to obtain a composite ceramic coating. S3. Add 1.2 wt.% polyvinyl alcohol to the aluminum sol prepared in Example 2, stir at 85°C until completely dissolved, and uniformly coat the composite ceramic coating surface. Then, perform a graded drying treatment: first dry at 60°C for 20 min, then dry at 80°C for 15 min, and then dry at 120°C for 15 min, repeating this process 3 times. After drying, perform vacuum sintering treatment: first heat treat at 120°C for 20 min, then heat treat at 240°C for 20 min, and then heat treat at 400°C for 30 min to obtain a modified composite ceramic coating. Then, grind and polish the obtained modified composite ceramic coating onto the original ceramic coating surface to prepare a highly sensitive coulomb force type alumina electrostatic chuck.

[0032] Comparative Example 2: A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck, comprising the following steps: S1. The surface of the electrostatic chuck is preheated to 150°C using a high-temperature flame stream. Then, using the modified nano-titanium dioxide mixed powder prepared in Example 1 with 1.5 wt.% high-purity alumina doped with it as raw material, an atmospheric plasma spraying process is performed on the preheated electrostatic chuck surface. The voltage is 60V, the current is 600A, the argon flow rate is 40NLPM, the hydrogen flow rate is 10NLPM, the spraying distance is 120mm, and the powder feeding rate is 30g / min to obtain a ceramic coating. S2. The ceramic coating was mechanically polished with SiC sandpaper, and then impurities were washed away with anhydrous ethanol. 2.77g of thiourea and 1.87g of sodium molybdate were dissolved in 80mL of deionized water and magnetically stirred for 30min to obtain a mixed solution. The polished ceramic coating was immersed in the mixed solution and sonicated for 10min. Then it was transferred to a vacuum drying oven and allowed to stand for 10min under a pressure of -0.095MPa. The immersion-pressure-standing step was repeated 3 times. Then it was transferred to a reaction vessel lined with polytetrafluoroethylene and reacted at 230℃ for 48h to obtain a composite ceramic coating. The obtained composite ceramic coating was then ground and polished onto the surface of the original ceramic coating to prepare a highly sensitive coulomb force type alumina electrostatic chuck.

[0033] Comparative Example 3: A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck, comprising the following steps: S1. The surface of the electrostatic chuck is preheated to 150°C using a high-temperature flame stream. Then, using the modified nano-titanium dioxide mixed powder prepared in Example 1 with 1.5 wt.% high-purity alumina doped with it as raw material, an atmospheric plasma spraying process is performed on the preheated electrostatic chuck surface. The voltage is 60V, the current is 600A, the argon flow rate is 40NLPM, the hydrogen flow rate is 10NLPM, the spraying distance is 120mm, and the powder feeding rate is 30g / min to obtain a ceramic coating. S2. The ceramic coating was mechanically polished with SiC sandpaper, and then impurities were washed away with anhydrous ethanol. 1.2 wt.% of polyvinyl alcohol was added to the aluminum sol prepared in Example 2, and stirred at 85°C until completely dissolved. The mixture was then uniformly coated onto the surface of the ceramic coating. A staged drying process was then performed, first drying at 60°C for 20 min, then drying at 80°C for 15 min, and then drying at 120°C for 15 min, repeated 3 times. After drying, vacuum sintering was performed, first heat-treated at 120°C for 20 min, then heat-treated at 240°C for 20 min, and then heat-treated at 400°C for 30 min to obtain a composite ceramic coating. The obtained composite ceramic coating was then polished onto the surface of the original ceramic coating to prepare a highly sensitive coulomb force type alumina electrostatic chuck.

[0034] Performance testing Please see Figure 2 , Figure 2 The cross-sectional morphology of the sample prepared in Example 4 of this application is determined by... Figure 2 It can be seen that the sample coating exhibits good uniformity, forming a dense film layer.

[0035] The high-sensitivity Coulomb force type alumina electrostatic chucks prepared in Examples 3-5 and Comparative Examples 1-3 were subjected to performance testing: 10 points were randomly and evenly selected on the cross-section of the sample surface, and hardness tests were performed using an HV-1000A microhardness tester (load 10N, holding time 10s). The average value of the test data was taken as the Vickers hardness value. The electrochemical corrosion friction performance of the composite coating was investigated using an MSR-2T electrochemical reciprocating friction and wear tester and a Chenhua CHI604e electrochemical analyzer. 316 balls (hardness ≤ HRC26) were selected as the paired balls. The experimental sliding speed was 4cm / s, the load was 5N, the friction time was 40min, and artificial seawater (Na, by mass concentration) was used. + 9.8~10.6 g / L, Mg 2+ 1.1~1.4g / L, Cl - 18.05~19.35g / L, SO4 2- 2.2~2.6g / L, K + 0.36~0.42g / L, Ca 2+ The corrosive solution was prepared at a concentration of 0.38~0.44 g / L. Before electrochemical friction, the sample surface was cleaned with anhydrous ethanol. In the electrochemical friction experiment, a saturated calomel electrode was used as the reference electrode, and a platinum electrode as the counter electrode. The corrosion time was 3000 s, followed by a 300 s rest period. The friction corrosion time was 2400 s, followed by a 300 s rest period after the friction was completed. After the corrosion friction was completed, nine points were randomly selected, and the cross-sectional area A (mm²) of the wear track was measured using a DSX510 three-dimensional profilometer. 2The wear rate was calculated by taking the average value, and the data results are shown in Table 1.

[0036] Table 1 Sample performance test results

[0037] As can be seen from the data in Table 1, the samples prepared in Examples 3-5 of this invention have high hardness and good wear resistance and corrosion resistance. In Comparative Example 1, modified nano-titanium dioxide was replaced with an equal amount of nano-titanium dioxide; in Comparative Example 2, polyvinyl alcohol-modified aluminum sol was not introduced; and in Comparative Example 3, molybdenum disulfide was not synthesized in situ. The measured Vickers hardness and corrosion resistance of Comparative Examples 1-3 were lower than those of Examples 3-5, while the wear rate was higher. This indicates that the samples prepared in Examples 3-5 have higher hardness, better wear resistance, and better corrosion resistance than those in Comparative Examples 1-3.

[0038] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0039] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A method for manufacturing a highly sensitive Coulomb force type alumina electrostatic chuck, characterized in that, Includes the following steps: S1. The surface of the electrostatic chuck is preheated to 100~200℃ using a high-temperature flame stream. Then, high-purity alumina doped with 1.3~1.8wt.% modified nano-titanium dioxide mixed powder is used as raw material to perform atmospheric plasma spraying on the preheated electrostatic chuck surface to obtain a ceramic coating. S2. The ceramic coating is mechanically polished with sandpaper, and then impurities in the polishing process are washed away with anhydrous ethanol. Thiourea and sodium molybdate are dissolved in deionized water and magnetically stirred for 30 minutes to obtain a mixed solution. The polished ceramic coating is immersed in the mixed solution and sonicated for 10 minutes. Then it is transferred to a vacuum drying oven and allowed to stand for 10 minutes under a pressure of -0.095 MPa. The immersion-pressure-standing step is repeated 3 times. Then it is transferred to a reaction vessel with a polytetrafluoroethylene liner and reacted at 230℃ for 48 hours to obtain a composite ceramic coating. S3. Add 1~1.5wt.% polyvinyl alcohol to the aluminum sol, stir at 85℃ until completely dissolved, and evenly coat it on the surface of the composite ceramic coating. Then, perform graded drying treatment, followed by vacuum sintering treatment to obtain a modified composite ceramic coating. Subsequently, grind and polish the obtained modified composite ceramic coating onto the surface of the original ceramic coating to prepare a highly sensitive coulomb force type alumina electrostatic chuck. The modified nano-titanium dioxide is prepared by purifying carbon nanotubes using nitric acid oxidation, and then coating the surface of the purified carbon nanotubes with a layer of nano-titanium dioxide particles using tetrabutyl titanate and purified carbon nanotubes as raw materials through an alkoxide hydrolysis method.

2. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The purity of the high-purity alumina is 99.999%.

3. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The particle size of the high-purity alumina is 25~50μm.

4. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The parameters for the atmospheric plasma spraying process are set as follows: voltage 60~70V, current 550~600A, argon flow rate 40~50NLPM, hydrogen flow rate 10NLPM, spraying distance 100~120mm, and powder feeding rate 25~30g / min.

5. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The thickness of the ceramic coating is 175~185μm.

6. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The preparation method of the modified nano-titanium dioxide includes the following steps: (1) Take carbon nanotubes and add them into a 68% concentrated nitric acid solution. Heat to 110°C and reflux for 12 hours. Then filter and wash with deionized water until neutral. Dry at 80°C to constant weight to obtain purified carbon nanotubes. (2) The purified carbon nanotubes were ultrasonically dispersed in a 1% sodium dodecyl sulfate aqueous solution, the water was removed by rotary evaporation and dried at 80°C. Tetrabutyl titanate was dissolved in a reactor containing an ethanol solution, and then the dried purified carbon nanotubes were added and ultrasonically vibrated for 5 min. The ultrasonically vibrated reactor was placed in a beaker containing deionized water, the mouth of the beaker was sealed with a plastic film, and the sealed beaker was placed in a water bath at 80°C for 10 h. The reaction product was washed with deionized water, filtered and dried at 100°C for 6 h, and finally calcined at 350°C for 2 h to prepare modified nano titanium dioxide.

7. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 6, characterized in that, The length of the carbon nanotubes is 8~14μm.

8. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 6, characterized in that, The ratio of purified carbon nanotubes, tetrabutyl titanate, and ethanol solution is 1g:3.3g:40mL.

9. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The mass ratio of thiourea to sodium molybdate is 1.48:

1.

10. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The preparation method of the aluminum sol includes the following steps: Aluminum nitrate solution was heated to 85°C in a constant temperature water bath. Ammonia solution was then added dropwise while stirring continuously until the pH value stabilized at 9.

1. The solution was then removed and cooled. After the temperature dropped to room temperature, the solution was centrifuged. The lower precipitate was collected, dissolved in deionized water, and nitric acid solution was added dropwise to adjust the pH value to 3. The solution was then heated to 85°C in a water bath and stirred for 1 hour. Finally, the solution was aged for 24 hours to prepare aluminum sol.

11. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 10, characterized in that, The concentration of the aluminum nitrate solution is 0.2 mol / L; the concentration of the ammonia solution is 2 mol / L; and the concentration of the nitric acid solution is 1 mol / L.

12. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 10, characterized in that, The centrifugation operation was performed at a speed of 5000 r / min for 5 min, and was repeated 3 times.

13. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The parameters for the graded drying process are set as follows: first, dry at 60°C for 20 min, then dry at 80°C for 15 min, and then dry at 120°C for 15 min, and repeat 3 times.

14. The method for manufacturing a high-sensitivity Coulomb force type alumina electrostatic chuck according to claim 1, characterized in that, The parameters for the vacuum sintering treatment are set as follows: first, heat treatment at 120°C for 20 minutes, then heat treatment at 240°C for 20 minutes, and then heat treatment at 400°C for 30 minutes.

15. A highly sensitive Coulomb force type alumina electrostatic chuck, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 14.